Mastering the Digital Frontier a Deep Dive Into Accountants Performance Amidst Challenges and Opportunities - Sriwijayanti, Hari; Gustina, Leni; Harini, Gustia (Universitas Tanjungpura, 2024)
This study explores the impact of digital transformation on accountants' performance at PT Nutrifood Indonesia - Padang, focusing on the mediation effects between challenges, opportunities, and performance outcomes. Using a quantitative approach with a sample of 70 accountants, the research applies path analysis to examine the direct and indirect relationships between these variables. The results reveal that digital transformation plays a significant role in mediating the effects of challenges and opportunities on accountants' performance. Challenges, such as regulatory changes and cybersecurity risks, drive digital adoption, while opportunities, like new technologies and innovative practices, further encourage it. These findings highlight that embracing digital transformation is crucial for improving efficiency, accuracy, and adaptability in accounting processes. The study concludes that to boost accountants' performance, organizations should foster a culture of innovation, leveraging technology to transform challenges into growth opportunities and ensuring sustained success in a rapidly evolving business landscape.Keywords: Digital Transformation, Accountants' Performance, Challenges, Opportunities